The Effect Of ZPT Types and Concentration on The Growth Of Kebiul Plant Cuttings (Caesalpinia bonduc L.) - Valen Heryanto; Ririn Harini; Fiana Podesta; Dwi Fitriani; Usman Usman (Universitas Muhammadiyah Sidoarjo, 2023)
The purpose of this study is to find out the effect of ZPT types and concentrations on the growth of cuttings of Kebiul plants (Caesalpinia bonduc L). The design used is a factorial complete randomized design (CRD) with 2 factors, namely the first factor is the type of Growth Regulatory Substance Giberelin, Auxin and Cytokinins, while the second is concentration control, 15 mg/l, 30 mg/l, and 45mg/l. Based on the tested levels of the two factors, 12 treatment combinations were obtained. Each treatment combination was repeated 3 times and 36 experimental units. The results of this study indicate that the interaction has no significant effect between the types of synthetic ZPT treatments and concentrations on all parameters and observations. The results of the study were analyzed using Analysis of Variety and if they had a significant effect, further tests were carried out using Duncan's Multiple Range Test (DMRT) at 5% level. Treatment of synthetic ZPT types significantly affected the length of shoots 9.12 WAP and the number of shoots 9 WAP, very significantly affected the number of shoots 3.12 MST, the number of leaves 9.12 WAP, root length and number of roots. Treatment Concentration had a significant effect on the number of shoots 9 MST, and the percentage of living cuttings, however it had a very significant effect on shoot length 3, 6, 9 MST, number of shoots 6, 12 MST, number of leaves 3, 6, 9 12 MST, root length and number of roots on Kebiul plant cuttings.